Analysis of the Potential of Green Sukuk in Infrastructure Finance in Aceh Province - Rico Dwi Cahyo; Elvitri Elvitri; Muammar Khaddafi; Iswadi Iswadi (LPPM UIKA Bogor, 2024)
Environmental problems are important because the quality of the environment will directly affect the quality of human life. In addition, the quality of the environment also affects the quality of human life in the future. Since 2018, Green Sukuk has been presented as a new alternative for people who want to invest their funds in bonds that combine the sharia system and use targets for companies that are promoting environmental care principles. It is also an alternative for local governments who need funding for infrastructure development in the region. This study aims to analyze the potential of Green Sukuk in infrastructure financing in the province of Aceh. The method used is descriptive qualitative. Sampling in this study uses a purposive sampling technique. This research is an analytical study with a SWOT analysis to determine the formulation in the preparation of long-term strategies. The population in this study are the stakeholders involved in uncovering the potential of green Sukuk in infrastructure financing in Aceh